Pengaruh Kepemimpinan Transaksional Guru sebagai Classroom Leader terhadap Kedisiplinan Siswa Kelas V di UPTD SD Inpres Kuanino 2 - Yukobsadi E. Boikope; Mbuik, Heryon Bernard; Hendrik, Hingrida Margarita Anastasia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by various forms of student indiscipline, including tardiness, noncompliance with school regulations, and delays in completing assignments. Teachers' transactional leadership is presumed to influence students' disciplinary behavior through the consistent implementation of classroom rules, supervision, and reinforcement strategies. This study aimed to determine the level of teachers' transactional leadership, the level of students' discipline, and the effect of teachers' transactional leadership on the discipline of fifth-grade students at UPTD SD Inpres Kuanino 2. The study employed a quantitative approach using an ex post facto research design. The population consisted of 27 fifth-grade students, all of whom were selected as the sample using a saturated sampling technique. Data were collected through observation, questionnaires, and documentation and analyzed using descriptive and inferential statistics. The results showed that teachers' transactional leadership at UPTD SD Inpres Kuanino 2 was categorized as good, with a mean score of 53.62. The data met the assumptions of normality and linearity, with Shapiro–Wilk significance values of 0.799 and 0.255 for the two variables and a Deviation from Linearity significance value of 0.620. Simple linear regression analysis revealed a significance value of 0.000 (< 0.05), indicating that teachers' transactional leadership has a positive and significant effect on student discipline. The regression coefficient was 0.815, and the coefficient of determination (R²) was 0.390, indicating that teachers' transactional leadership contributed 39% to student discipline, while the remaining 61% was influenced by other factors not examined in this study.